PUBLICATIONS OF THE WEEK. (Bookseller, 2002)
Presents a list of books published in the year 2002. 'Tibetan Sacred Art: The Heritage of Tantra,' by Detlef Ingo Lauf; 'Great Diamonds of India,' by Monisha Bharadwaj; 'Art From Thailand,' edited by Robert Brown; 'Orissa Revisited,' edited by Pratapaditya Pal.